METHODS OF CORRECTING GRAMMATICAL ERRORS (Journal of Universal Science Research, 2025)
Grammatical error correction plays a crucial role in developing learners’ accuracy and overall language proficiency in foreign language classrooms. This article explores the main methods of correcting grammatical errors, including explicit correction, implicit correction, recasts, elicitation, peer correction, and self-correction. It discusses how each method influences learners’ awareness, motivation, and long-term language development. The study highlights the importance of selecting appropriate correction techniques based on learners’ proficiency level, learning context, and instructional goals. Special attention is given to balancing accuracy and fluency, as excessive correction may hinder learners’ confidence and communicative competence. The findings suggest that a combination of corrective methods, rather than reliance on a single approach, is most effective in promoting grammatical accuracy while maintaining learner engagement. The article concludes that thoughtful and context-sensitive grammatical error correction enhances both teaching effectiveness and learner autonomy in EFL classrooms.